Kesiapan Dosen Dalam Pembelajaran Menggunakan E-Learning - Fandianta Fandianta; Herry Hermansyah; Refai Refai (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The implementation of learning using e-learning must be supported by several readiness factors. Organizational readiness factors, such as regulations, infrastructure, technology, and policies, have a significant effect on learning outcomes using e-learning. However, the human element in its use is also the most important factor in online learning. This research was conducted to measure the readiness of lecturers using e-learning on several factors, namely; Technology access factor, skill and training factor, instructor attitude factor. The sample of this study was 100 active lecturers. Univariate data analysis was performed by calculating the average readiness index and frequency and identifying categories of readiness intervals for using e-learning. The results of this study show the readiness of lecturers in using e-learning assessed from technology mastery factors, skill and training factors, and instructor attitude factors. However, for a very mature level, refinement and development of all these factors are still necessary. In addition, the training aspect is considered quite ready, but management must open training opportunities for lecturers to run online classes.